2019
DOI: 10.3390/md17040220
|View full text |Cite
|
Sign up to set email alerts
|

Marine Fungi from the Sponge Grantia compressa: Biodiversity, Chemodiversity, and Biotechnological Potential

Abstract: The emergence of antibiotic resistance and viruses with high epidemic potential made unexplored marine environments an appealing target source for new metabolites. Marine fungi represent one of the most suitable sources for the discovery of new compounds. Thus, the aim of this work was (i) to isolate and identify fungi associated with the Atlantic sponge Grantia compressa; (ii) to study the fungal metabolites by applying the OSMAC approach (one strain; many compounds); (iii) to test fungal compounds for their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 85 publications
0
62
0
Order By: Relevance
“…Atlantic sponge (Grantia compressa)-associated fungus, Eurotium chevalieri MUT 2316 (West Coast of Ireland), produced 10 metabolites with promising antibacterial (Table 3) ( Figure 4A) as well as antiviral activities [106]. This study demonstrated and reaffirmed that "One strain, many compounds" (OSMAC) is a powerful method to stimulate and enhance the production of an incredible variety of new secondary metabolites.…”
Section: Invertebrate-associated Fungi (Sponges Ascidians Crab)mentioning
confidence: 62%
See 1 more Smart Citation
“…Atlantic sponge (Grantia compressa)-associated fungus, Eurotium chevalieri MUT 2316 (West Coast of Ireland), produced 10 metabolites with promising antibacterial (Table 3) ( Figure 4A) as well as antiviral activities [106]. This study demonstrated and reaffirmed that "One strain, many compounds" (OSMAC) is a powerful method to stimulate and enhance the production of an incredible variety of new secondary metabolites.…”
Section: Invertebrate-associated Fungi (Sponges Ascidians Crab)mentioning
confidence: 62%
“…Structures of (A) physcion (3), dihydroauroglaucin (4), and isodihydroauroglaucin (6)[106]; and (B) dolabellane-type diterpenoids (1−3) and three new atranones (4)[110].…”
mentioning
confidence: 99%
“…Broadening the knowledge of marine fungi associated with a vast range of biotic and abiotic substrates is becoming more and more important. The reason behind this lies in the ecological relevance that these organisms may play in the oceans and in their possible exploitation as a source of potentially novel enzymes and bioactive compounds (Bovio et al, 2019;Grossart et al, 2019;Overy et al, 2019;Youssef et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Marine-derived filamentous fungi are a well-known source of pharmaceutically relevant molecules, previously showing antiviral, antibacterial, anticancer and other bioactivities [40,41]. Particularly promising is the Penicillium genus, which showed an extraordinary and unexploited potential to synthetize novel secondary metabolites [42].…”
Section: Discussionmentioning
confidence: 99%